Reuse of water from real reactive monochromic and trichromic wastewater for new cotton dyes after efficient treatment using H2O2 catalyzed by UV light. Issue 4 (August 2021) - Bezerra, Katia Crystina Hipólito; Fiaschitello, Ticiane Rossi; Labuto, Geórgia; Freeman, Harold S.; Fragoso, Wallace Duarte; da Costa, Sirlene Maria; da Costa, Silgia Aparecida
Abstract: The textile industry widely uses reactive dyes to obtain cotton fabrics having good resistance to color removal despite frequent washing. This level of dye usage generates substantial volumes of wastewater containing significant quantities of residual dye requiring treatment before discharges from commercial dyeing operations to public waterways. As part of a study aimed at recycling/reusing rather than discharging reactive dye wastewater, well-known dyes Reactive Yellow 176, Reactive Red 241, and Reactive Blue 221 were used in dyeing cotton fabric, and the generated wastewater samples were decolorized with H2 O2 catalyzed by UV light. The efficiency of UV/H2 O2 decolorization for trichromic wastewater was determined by UV-Vis monitoring at 550 nm, wherein it was found that more than 91% of color removal in trichromic wastewater occurred at pH 4. The reuse of wastewater was investigated by a total of three sequential cycles of wastewater treatments. The quality of cotton dyed with reused wastewater was assessed through color measurements using CIELAB, fastness to light, and wash fastness testing. Results showed that MCT/VS-based reactive dye wastewater arising from UV/ H2 O2 treatment could be used for two subsequent dyeing cycles without compromising the quality of the color of the dyed cotton fabrics. The proposed treatment can also save water and salt, enhancing the economy of the dyeing process. Graphical abstract: ga1 Highlights: Monochromic and trichomic dyes textile wastewaters were treated by UV/H2 O2 . pH 4 was the best to treat the wastewater removing more than 90% of color. The treated wastewater was efficiently used for two cycles of cotton fabric dyeing. CIELAB, fastness to light, and reuse washing testing attested the dyeing quality.